History of medical education in Myanmar - Tayzar Hein; Ye Phyo Aung; Khin Aung Htun; Tin Tun (The Asia Pacific Scholar)
Introduction: The medical education system of Myanmar has evolved through a dynamic history influenced by colonial legacies, national development efforts, and global collaborations. This article explores the progression of medical education in Myanmar, focusing on its historical milestones, challenges, and advancements in response to societal and healthcare needs. Method: This study is based on a comprehensive review of historical records, policy documents, and academic literature, with "A Concise History of Medical Education in Myanmar" by Aung Than Batu as a primary reference. Key milestones, collaborations, and innovations were analysed to trace the evolution of medical education from the colonial period (1907) to the present day. Quantitative data, including the number of medical universities, training durations, and infrastructure developments, were included for a clearer perspective. Results: The analysis highlights transformative milestones, including the establishment of the first medical school in 1907 and Rangoon Medical College in 1927. Over time, Myanmar has adapted to challenges such as resource constraints and political instability by fostering international collaborations and leveraging technology. Teaching methods have evolved significantly, integrating modern technologies alongside traditional pedagogies. Conclusion: Myanmar’s medical education exemplifies resilience and adaptability. By aligning its system with global standards, fostering research, and leveraging international expertise, the nation continues to contribute to global medical education and healthcare. This narrative serves as an inspiration for countries navigating similar challenges in medical education.